Skrining Novel Prebiotik Selective Fermentation Initiator (SFI) Untuk Bakteri Probiotik Elektrogenik Kulit - Prakoso Adi; Rizka Mulyani; John Jackson Yang (Sekolah Vokasi, Universitas Sebelas Maret, 2022)
The ability of electrogenic bacteria to generate electricity has been widely reported. In some cases of bacteria, the electricity production comes from the bacterial fermentation process of SFI compounds by these bacteria. Later, the resulted electrons are transferred out from inside to extracellular recipient molecules. Among of these studies has shown the ability of gram-positive bacteria S. epidermidis ATCC 12228 in terms of SFI compounds utilization to increase bacterial electron production and its application in the medical field. Based on these studies, the discovery of new SFI compounds becomes interesting to be explored. In this study, a new SFI compound was screened from 24 different compounds. The screen was initiated by testing the ability of these compounds to increase the fermentation activity of S. epidermidis ATCC 12228 in a 96-well plate. Determination of SFI compound was carried out by checking the exclusivity of the compound to increase the fermentation activity of S. epidermidis ATCC 12228. The selected SFI compound was then tested for cytotoxicity against this bacterium and its ability to increase the electron production of S. epidermidis ATCC 12228 using a microbial fuel cell (MCF). This study was successfully demonstrated the non-toxic properties of p-coumaric acid, also the ability of this compound to increase the fermentation activity and electron production of S. epidermidis ATCC 12228. This research is expected to be the first step to find another novel SFI compounds that will be useful in certain fields in the future.